Corporate social responsibilities and its contribution to employment rate in Malaysia / Siti Hartinie Mohammad (Faculty of Business and Management, 2008)
This research is study on the Corporate Social Responsibilities (CSR) and its contribution to employment rate in Malaysia. Purpose of the research is to identify activities that comprises in CSR and factors motivate firms to implement CSR. Research is conducted from the view of the firms that runs business in Malaysia. A total of 30 companies were selected as a respondent to answer the questionnaire. The objectives of this study are to identify most influence factors of CSR activities, to determine the activities that can be used as medium to implement CSR, and to find out the contribution of CSR to employment rate in Malaysia. From the data collected that have been analyzed through Statistical Package for Social Science (SPSS) software, it can be concluded that CSR is important in contributing to employment rate in Malaysia.